PEMBUATAN DAN UJI SIFAT FISIK GEL ANTINYERI KOMBINASI MINYAK ATSIRI BUNGA CENGKEH ( Syzygium aromaticum(L.) Merr.&Perry ) DAN SEREH (Cymbopogon nardus L. Rendle): PEMBUATAN DAN UJI SIFAT FISIK GEL ANTINYERI KOMBINASI MINYAK ATSIRI BUNGA CENGKEH ( Syzygium aromaticum(L.) Merr.&Perry ) DAN SEREH (Cymbopogon nardus L. Rendle) - Purgiyanti Purgiyanti; Inur Tivani (jurnal ilmiah manuntung sekolah tinggi ilmu kesehatan samarinda, 2019)
Clove and lemongrass are agricultural commodities that have high economic value. One of the natural compounds produced from both and is usually obtained by distillation is essential oil. The use of clove oil and citronella oil that has often been used by the public is as an analgetics. The purpose of this study was to make an analgetics gel from a combination of essential oils of clove and citronella oil with variations in the concentration of CMC-Na as a gelling agent and to determine the gel that wasmost preferred by respondents. This research is an experimental research, the method of document collection uses qualitative and quantitative data from laboratory experiments. The resulting gel is then tested for physical properties of the preparation which includes organoleptic test, homogeneity, pH, clarity, dispersion , protection power, and adhesion. Test of preference for 10 respondents to determine the most preferred gel. The results showed that the gel combination of clove and citronella oil with 2% CMC-Na concentration was the best formula seen from the physical test and preference test.